2016
DOI: 10.1016/j.artint.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Broken triangles: From value merging to a tractable class of general-arity constraint satisfaction problems

Abstract: International audienceA binary CSP instance satisfying the broken-triangle property (BTP) can be solved in polynomial time. Unfortunately, in practice, few instances satisfy the BTP. We show that a local version of the BTP allows the merging of domain values in arbitrary instances of binary CSP, thus providing a novel polynomial-time reduction operation. Extensive experimental trials on benchmark instances demonstrate a significant decrease in instance size for certain classes of problems. We show that BTP-mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…In fact we will show that a more general class of problems, introduced by Cooper et al [17] and known as DGABTP, is decided by GAC. Cooper et al [17] showed that this class of problems has a polynomial-time solution algorithm based on variable elimination. Using Theorem 3 it is relatively simple to show that this class is also decided by GAC.…”
Section: Proposition 1 Any Instance I Whose Constraint Relations Are mentioning
confidence: 99%
See 3 more Smart Citations
“…In fact we will show that a more general class of problems, introduced by Cooper et al [17] and known as DGABTP, is decided by GAC. Cooper et al [17] showed that this class of problems has a polynomial-time solution algorithm based on variable elimination. Using Theorem 3 it is relatively simple to show that this class is also decided by GAC.…”
Section: Proposition 1 Any Instance I Whose Constraint Relations Are mentioning
confidence: 99%
“…These are the instances satisfying the so-called broken-triangle property. CSP instances satisfying the BTP (or its various extensions [17]) are the only known examples of classes of instances decided by GAC which are not closed under the action of removing a constraint, as the next example illustrates. {(2, 0), (2, 1), (2, 2), (1, 2)}.…”
Section: Hybrid Restrictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the path concerned (denoted as p), D is defined on the basis of the acceptable ranges of the variables. One solution to the problem is a set of values to instantiate each variable within its domain, denoted as {<x 1 , V 1 >,<x 2 , V 2 >,…,<x i , V i >,<x i+1 , V i+1 >,…,<x n , V n >}(V i ∈D i ) to make p feasible, which means that each constraint in R should be satisfied [4].…”
Section: Introductionmentioning
confidence: 99%